2015
DOI: 10.1080/11956860.2015.1047140
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal changes in oases in the Heihe River Basin of China: 1963–2013

Abstract: Artificial oases have flourished as human activities have intensified. Changes in oases in the Heihe River Basin are typical for the arid areas of China. Based on images from 14 separate periods during 1963-2013 that were compiled from multi-sensors, data on the boundaries of oases were extracted using the methods of object-oriented image segmentation and Normalized Difference Vegetation Index thresholds as well as visual interpretation. Based on extracted data, the spatio-temporal changes in oases were analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…This study showed that the total oasis area increased in the Hexi Corridor over the past 30 years. This result is consistent with the results reported in HHRB [9], in SYRB [35] and in SLRB [53]. The trend was similar in other arid areas such as the Sangong River basin and the Hotan oasis [54] of Xinjiang in north-west china [55].…”
Section: Major Driving Forces Of the Oasis Spatio-temporal Changesupporting
confidence: 92%
See 3 more Smart Citations
“…This study showed that the total oasis area increased in the Hexi Corridor over the past 30 years. This result is consistent with the results reported in HHRB [9], in SYRB [35] and in SLRB [53]. The trend was similar in other arid areas such as the Sangong River basin and the Hotan oasis [54] of Xinjiang in north-west china [55].…”
Section: Major Driving Forces Of the Oasis Spatio-temporal Changesupporting
confidence: 92%
“…Changes in oases over time are characterized by the rate of change between the start and end times [34,35]. LULC change models, such as the single dynamic degree (SDD) model and the bidirectional dynamic degree (BDD) model, are widely used to analyze changes in oases [2,9,34]. The SDD model describes the rate of net change, but it neglects the increasing and decreasing components during the evolution.…”
Section: Oasis Changes Over Timementioning
confidence: 99%
See 2 more Smart Citations
“…An oasis is an isolated green fertile land in a desert that often surrounds a water source such as a spring; it provides habitat for animals, and sometimes humans (Xie et al, 2015). The main landscapes of oases in Morocco are vegetation especially palm trees, rivers and settlements.…”
Section: Introductionmentioning
confidence: 99%